Overall structure of Au12Ag60(S-c-C6H11)31Br9(Dppp)6: achieving a stronger assembly of icosahedral M13 units. Issue 6 (24th January 2023) - Zhou, Manman; Li, Kang; Wang, Pu; Zhou, Huimin; Jin, Shan; Pei, Yong; Zhu, Manzhou
Abstract : [Au12 Ag60 (S- c -C6 H11 )31 Br9 (Dppp)6 ]Br2 has provided a breakthrough in icosahedral assemblies, i.e., achieving a twelve-mer assembly, helping to elucidate the fusion growth of M13 -based assembled nanoclusters and their geometric/electronic structure correlations. Abstract : Precise atomically assembled nanoclusters provide a great platform to elucidate the evolution of the assembly of building blocks. Herein, a large icosahedral (M13 )-based silver–gold alloy nanocluster [Au12 Ag60 (S- c -C6 H11 )31 Br9 (Dppp)6 ]Br2 (dppp = 1, 3-bis(diphenylphosphino)propane) is reported. Structurally, Au12 Ag60 consists of an Au12 Ag40 kernel, which is viewed as the interpenetration of ten twisted complete icosahedrons (M13 ) and two missing icosahedrons (M12 ), and this is surrounded by a complex metal–organic shell. Benefiting from the extra doping of eight to twelve Au atoms, the octameric assembly was increased to a twelve-mer assembly. The time-dependent density functional theory (TDDFT) method with a Tamm–Dancoff approximation (TDA) was performed to investigate the difference in the optical properties of Au12 Ag60 and Au8 Ag57 . The results indicate that the difference in the amount of Au atoms results in different optical properties. Furthermore, transient absorption spectroscopy (TA) was also performed, revealing that a twelve-mer assembly greatly enhances the excited-state lifetime. The [Au12 Ag60 (S- c -C6 H11 )31 Br9 (Dppp)6 ]Br2 alloy nanocluster has provided a breakthrough in the number of icosahedral M13 assemblies, i.e., achieving a twelve-mer assembly, helping to elucidate the fusion growth of M13 -based assembled nanoclusters as well as their geometric/electronic structure correlations, which will promote further research on the assembly of M13 nano-building blocks, especially on their optical properties.